ASYLUM AND DETENTION. THE GUATEMALANS OF 1954 IN PERON’S ARGENTINA - Rostica, Julieta Carla (2015)
After the coup of June 1954, in Guatemala there was a mass political asylum. The Argentine government received about two hundred people, including leading figures of the Guatemalan Labor Party. However, a few days after arriving in the country, a group of over thirty Guatemalans were arrested and imprisoned in the prison of Villa Devoto. The article seeks to address three dimensions, from the perspective of historical sociology, which allow to account for the conditions of possibility of this event: ideology, law and foreign policy of the government of Juan Domingo Perón. The work will allow us to explore the complexity and ambiguity that characterized the classical populism in Latin America and will be an excuse to relocate the fifties, usually overshadowed by the sixties and seventies, as critical juncture to explain the historical conditions of the political violence in Latin America.